Heat transfer performance of Al2O3-TiO2-SiO2 ternary nanofluids in plain tube with wire coil inserts - Anwar Ilmar Ramadhan; Efrizon Umar; Wan Hamzah Azmi; Alvika Meta Sari (Mechanical Engineering for Society and Industry, 2024)
The ternary nanofluids are considered due to their advantages in overcoming the stability drawback of mono and binary nanofluids. This study aims to heat transfer performance of Al2O3-TiO2-SiO2 ternary nanofluids in plain tube with wire coil under experimental. The ternary nanofluids were formulated using the composition ratio of 20:16:64 by volume in various volume concentrations ranging from 0.5 to 3.0%. Thermal conductivity and dynamic viscosity of ternary nanofluids were measured with KD2 Pro Thermal Properties Analyzer and Brookfield LVDV III Rheometer. Experimental forced convection heat transfer was carried out using a fabricated setup for Reynolds numbers from 2,300 to 12,000 at bulk temperature of 70 °C in plain tubes with wire coil inserts (0.83 ≤ P/D ≤ 2.50). Experimental results are highest thermal conductivity enhancement of 24.8% was obtained for ternary nanofluids at 3.0% volume concentration. The 3.0% volume concentration also shows the highest viscosity at all temperatures. The maximum heat transfer improvement for ternary nanofluids in a plain tube with wire coil (P/D-0.83), was attained by 3.0% volume concentration of up to 199.23%. The average TPF of the wire coil increases compared to the plain tube and improves further with volume concentrations in the range of 2.39 to 2.84.